Understanding the Role of Finance in Sustainable Development: A Qualitative Study on Environmental, Social, and Governance (ESG) Practices - Junaedi, J. (Manunggal Halim Jaya, 2024)
This qualitative literature review investigates the multifaceted landscape of sustainable finance, aiming to provide insights into its key dimensions and implications for sustainable development. The research methodology involves a comprehensive examination of existing literature utilizing qualitative analysis techniques such as thematic analysis, content analysis, and narrative synthesis. The study explores environmental considerations, social dimensions, and governance practices within sustainable finance, drawing on diverse perspectives from academic literature, industry reports, and policy documents. Key findings reveal the pivotal role of sustainable finance in advancing environmental objectives by mobilizing capital towards environmentally sustainable projects, promoting conservation, and facilitating the transition to a low-carbon economy. Moreover, the study highlights the significance of addressing social issues such as labor rights, gender equality, and community development through sustainable finance initiatives. Additionally, effective governance practices are identified as essential for ensuring transparency, accountability, and ethical conduct within the financial sector. The implications of sustainable finance extend beyond financial markets, encompassing environmental outcomes, social equity, and governance frameworks crucial for achieving sustainable development goals. Despite challenges such as data availability, standardization, and regulatory coherence, sustainable finance presents opportunities for innovation and collaboration to address pressing global challenges. Overall, this study contributes to a deeper understanding of sustainable finance and underscores its potential to drive positive change towards a more resilient, inclusive, and sustainable global economy.